SpikingBrain and Mistral 7B Throughput in Long-Context Code Completion - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 10 peer-reviewed papers addressing the following research question: How does the throughput of SpikingBrain compare to Mistral 7B with sliding window attention on long-context code completion tasks exceeding 10k tokens. 13 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.5/10. This report is a machine-generated literature synthesis and
Machine-generated literature synthesis.